The Contribution of Information and Communication Technology to the wellbeing of the urban poor in South Africa - Allen, Michaella (School of Economics, 2019)
Within the context of an increasingly pervasive digital society, this study seeks to understand the extent to which Internet-enabled mobile phones contribute towards the social and economic inclusion or exclusion of the urban poor in South Africa. This stems from the growing recognition that although mobile phones may be tools for opportunity and development, access to these devices may not be sufficient to ensure that they are used optimally for development. Stubbornly high mobile broadband prices and ineffectual policy reform in South Africa alternatively risk not only inhibiting meaningful ICT usage by the poor, but also potentially exacerbating their current economic marginalisation through digital exclusion. To analyse the relationship between mobile phone usage and urban poor development, Roxana Barrantes’ demand-focused Digital Poverty Framework is quantitatively applied to nationally representative data from the 2017 “Beyond Access” Research ICT Africa Household and Individual ICT access/usage survey. Results indicate that only percent 12 percent of urban individuals at the Bottom of the Economic Pyramid (BoP) are capable of actively using their Internet-enabled mobile phones on a daily basis in meaningful ways. Although all Internetenabled mobile phone users at the urban BoP are capable of using their devices to strengthen their economic, social and human capabilities; optimal usage is only predicted with a 5 percent probability in terms of both daily use and quality of opportunities generated for improved wellbeing. Accounting for the confounding presence of students, a Generalised Ordered Logit regression identifies digital literacy and mobile broadband affordability as primary barriers to the optimisation of Internet-enabled mobile phone use. In spite of ongoing regulatory pressure on operators to reduce prices, these findings highlights the current inefficacy of these efforts to promote greater digital inclusion among the mobile-data dependent urban BoP. This failure suggests a critical need for State policies to improve the viability of complementary and free aggregated access to mobile broadband alternatives, such as Free Public Wi-Fi, that can optimise the developmental potential of mobile phones for the urban poor. Such policies that additionally address digital skills needs of the poor are even better suited to equip the State to tackle key barriers of digital literacy and awareness as arguably more intractable problems to promoting effective ICT use and digital equality.